2019
DOI: 10.1002/ffj.3547
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and release mechanism of lavender oil microcapsules with different combinations of coating materials

Abstract: The aim of the work was to control morphology and release of lavender oil (LO) microcapsules produced using spray drying through different combination of coating materials (gum acacia, sodium caseinate, gelatin, chitosan, β‐cyclodextrin and polyvinyl alcohol). In addition, the properties of LO microcapsules including encapsulating efficiency (EE), loading capacity, mean particle size and morphology were characterized. Results displayed that the ternary formulations showed higher EE than the pure and binary mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…94,95 The advantage of combining GA and CH is evident in the study of Zhang et al which evaluated the encapsulation of lavender oil using GA and other materials (sodium caseinate, gelatin, CH, β-cyclodextrin, and PVA). 96 The employment of pure GA resulted in an encapsulation efficiency of around 20% while GA-CH microcapsules presented an encapsulation efficiency of 31%. The loading capacity and the release rate were also improved for the GA-CH combined microcapsule.…”
Section: Gum Arabicmentioning
confidence: 98%
“…94,95 The advantage of combining GA and CH is evident in the study of Zhang et al which evaluated the encapsulation of lavender oil using GA and other materials (sodium caseinate, gelatin, CH, β-cyclodextrin, and PVA). 96 The employment of pure GA resulted in an encapsulation efficiency of around 20% while GA-CH microcapsules presented an encapsulation efficiency of 31%. The loading capacity and the release rate were also improved for the GA-CH combined microcapsule.…”
Section: Gum Arabicmentioning
confidence: 98%
“…Previous research has reported that the encapsulation of pesticides into polymeric carriers could achieve continuous and stable release of active ingredients, which provided enhanced efficacy and reduced the impacts on the environment. The microcapsules have many advantages compared to traditional pesticide formulations, which include lower toxicity and environmental pollution and higher storage stability. , Among various microencapsulation methods, interfacial polymerization has been widely used to encapsulate pesticides because of its simple process, low preparation cost, and outstanding application properties . The shell material is one of the most important components because it is a crucial factor that influences the structure, permeability, controlled release, and thermal stability of the microcapsules. , A survey of the literature indicates that polyurea, polyurethane, and epoxy resin are usually selected as the microcapsule shell for interfacial polymerization. , Especially, polyurea is a unique polymer with physical properties and chemical stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, inspired by our previous works on the controllable preparation of microcapsules [37][38][39] and on SACs, 20,40,41 we proposed a facile and efficient synthesis method by utilizing bulk emulsification and pendant drop technologies, to quasi-continuously synthesize S, N codoped carbon supported SACs (M/SNC, M=Fe, Ni, Co). This strategy includes three steps, (a) the continuous synthesis of metal precursor microcapsules encapsulated by chitosan (CS)/sodium dodecyl sulfate (SDS) hydrogel, and then followed by (b) pyrolysis and (c) acid washing.…”
Section: Introductionmentioning
confidence: 99%